Structural studies of the pectic polysaccharide from fruits of Punica granatum. (1st May 2020) - Shakhmatov, Evgeny G.; Toukach, Philip V.; Makarova, Elena N.
Highlights: Structure of P. granatum pectin (PGO ) was characterized for the first time. PGO core consists of 1, 4-α-Gal p A, 1, 4-α-Gal p A( O Me), and 1, 4-α-Gal p A( O Ac). RG-I side chains are formed of branched 1, 5-α-l -arabinan and arabinogalactan type I. PGO fraction also contained of the glucuronoxylan and xyloglucan. Abstract: The polysaccharide PGO containing 76 % of uronic acids, was obtained from peels and membranes of Punica granatum fruits by extraction to the aqueous solution of (NH4 )2 C2 O4 . The chemical structure of PGO was characterized by enzymatic and partial acid hydrolyses, Smith degradation and 1D/2D NMR spectroscopy. It has been found that PGO consisted mainly of highly methyl-esterified and lowly acetylated pectin. Backbone of the macromolecule was represented by 1, 4-α-D-Gal p A, 1, 4-α-D-Gal p A( O Me), 1, 4-α-D-Gal p A( O Ac). The branched region PGO contained minor segments of partially acetylated rhamnogalacturonan-I (RG-I). RG-I side chains were comprised of highly branched 1, 5-α-l -arabinan and segments of arabinogalactan type I. In addition to pectins, PGO contained the glucuronoxylans and xyloglucans, indicating a close interaction of these polysaccharides with each other in the cell wall. It was concluded that P. granatum fruit could be a promising source of pectic polysaccharides.